PENGOLAHAN LIMBAH CAIR KEGIATAN EKPLORASI MINYAK DAN GAS BUMI DENGAN METODE COMPREHENSIVE SOLUTION (BIOREMEDIASI, BIOTREAMENT DAN BIO FILTRASI) - Chasri Nurhayati (Jurnal Dinamika Penelitian Industri, 2010)
Research about treatment of waste water from activity of Exploration and production oil and Gas with comprehensive solution method (bioremediation-biotreatment-biofiltration) has been done. Purpose of this research is to knows the bacterium activity in reducing rate cemaran petroleum liquid waste.. first phase added bioremiaddiasi with addition of biological agent which has been obtained. At this phas added bacterium counted 6% v/v from waste water volume and growth of bacterium is optimal. Second phase is biotreament that is by giving opportunity of bacterium which has been added so that initiation of floc formation. At this phase liquid waste is flown showly and is not aerated so that s formed flok initiation by bacterium, and than phase three is biofiltration by flowing waste to bioreactorending containing active carnonl. The active carbon has contained bacterium at part of the surface so that liquid waste passingit will experience biofiltration. The three steps can process waste soThat so parameter qualified that is H²S,Fenol,COD,Oil fatty, and ammonia declines so is under theasthold with quicker time.To know method effectiveness of comprehensive solution is done waste treatment of microcosm scale to apply biological agent obtained.. This thing was showed result of examination of control microcosm from sampling T0 until T8 is H2S:0.144-0,015 mg/l,phenol 1,6537-0,405 mg/l,hydrogen ion exponent 9,07-9,13,COD g372-1132 mg/l, oil lemak52-471 mg/l and ammonia 3,713-0,1373 mg/l of chemical test result at microcosm with method coprehensive solution is H2S: 0,160-0,014 mg/l,phenol 0,0529-0,0105mg/l,hydrogent ion exponent 9,07-9,13,COD 9372-1132 mg/l, oil lemak 52 -471 mg/l and ammonia 3,713-0,1373 mg/l.Based on calculaton of linear regresision to degradation of parameter tasted waste at microcosm with method comprehensive solution is estimated to requires processing time around 41 days, almost thrice more effectively if using ordinary IPAL method